2005
DOI: 10.1007/bf03054382
|View full text |Cite
|
Sign up to set email alerts
|

Ecodesign — design and evaluation of an e-learning system for vocational training

Abstract: Summary:At the Vienna University of Technology an online course in sustainable product design has been developed. The aim of this course is to offer vocational training for professionals in product design. The interface of the e-learning system is easy to understand. The whole system is adapted to the needs of the target group. Communication and cooperation play an important role for the e-learning system. Extensive evaluation is supposed to ensure the effectivity of the system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…The current findings showed that educational, geographical, social, economic, and even physical aspects of learners have not been taken into consideration sufficiently in current educational processes and practices, including learning styles, ability to control learning progress and records, and the application of diverse strategies for teaching and assessing students' academic achievement. These findings are aligned with previous studies (20,21,23,25,43,(45)(46)(47)(48)55).…”
Section: Educational Approachessupporting
confidence: 82%
“…The current findings showed that educational, geographical, social, economic, and even physical aspects of learners have not been taken into consideration sufficiently in current educational processes and practices, including learning styles, ability to control learning progress and records, and the application of diverse strategies for teaching and assessing students' academic achievement. These findings are aligned with previous studies (20,21,23,25,43,(45)(46)(47)(48)55).…”
Section: Educational Approachessupporting
confidence: 82%
“…To obtain a comprehensive picture of the whole system, such methods of investigation would take much more time than 1 h. Therefore, it was decided not to use them. In previous studies, software logs [26,31] were used. The data from software logs is interesting, in that it is possible to monitor what learners actually do in a natural setting and without influence by the investigator.…”
Section: Results From Interviewsmentioning
confidence: 99%
“…Blended learning as a result of the development of information and communication technology in the learning system has been widely applied to vocational education programs (Bliuc et al, 2012;Pohl et al, 2005;Yang et al, 2015;Yalcinkaya, 2015;Stapa et al , 2014;Groschl et al, 2015). Given the technical education held at the Faculty of Engineering, State University of Malang including vocational education, the instructional design follows several indicators as follows such as: a) aspects of needs analysis, b) selection and order of competence, c) learning development, and d) evaluation of learning (Triyono, 2015: 61).…”
Section: Literature Reviewmentioning
confidence: 99%